2011
DOI: 10.1097/olq.0b013e31821a4f43
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Prevalence Is Increasing Among Men Who Have Sex With Men in China: Findings From a Review and Meta-Analysis

Abstract: Significant increases in HIV prevalence among MSM were consistently observed across all Chinese regions. There is an urgent need for implementation of effective public health interventions to curb the spread of HIV infection among MSM across China, especially in the Southwest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 28 publications
6
90
0
Order By: Relevance
“…5 From 2009 to 2011, several metaanalysis of HIV among Chinese MSM reported pooled HIV prevalence as 2.5%-15.8%. [6][7][8][9] Growing studies suggest that not only individual factors [10][11][12] (biologic, demographic and risk behaviours), but also social factors [13][14][15] (cultural context, social networks, neighborhood effects and social capital) and structural factors 16 (structural violence and discrimination, legal structures, demographic change, the policy environment and war and militarisation) influence the risk of HIV acquisition, disease progression, distribution of HIV/AIDS in population subgroups and HIV transmission dynamics. Hefei, the capital city of Anhui Province, links the centre and the east of China.…”
Section: Introductionmentioning
confidence: 99%
“…5 From 2009 to 2011, several metaanalysis of HIV among Chinese MSM reported pooled HIV prevalence as 2.5%-15.8%. [6][7][8][9] Growing studies suggest that not only individual factors [10][11][12] (biologic, demographic and risk behaviours), but also social factors [13][14][15] (cultural context, social networks, neighborhood effects and social capital) and structural factors 16 (structural violence and discrimination, legal structures, demographic change, the policy environment and war and militarisation) influence the risk of HIV acquisition, disease progression, distribution of HIV/AIDS in population subgroups and HIV transmission dynamics. Hefei, the capital city of Anhui Province, links the centre and the east of China.…”
Section: Introductionmentioning
confidence: 99%
“…A dramatic increase in the incidence of sexually transmitted diseases (STDs), such as gonorrhea (1), syphilis (1,2), and HIV seroconversion (3,4), has been reported worldwide. The gold standard for syphilis diagnosis remains the serology test, particularly the Venereal Disease Research Laboratory (VDRL) test or rapid plasma reagin (RPR) test (5,6).…”
mentioning
confidence: 99%
“…[2][3][4] In particular, the HIV prevalence rate of MSM is climbing at an alarming rate; as reported, the national HIV prevalence among MSM increased rapidly from 1.4% to 5.3% between 2001 and 2009 and this increasing trend is likely to continue in coming years. 5 Other studies have shown that HIV prevalence rates among sampled MSM were as high as 10.9% in 2006 and 20.9% in 2009 in some cities of southwestern China, which indicated that the HIV epidemic among MSM in China has reached crisis proportions in certain areas and that MSM are a key target populations for future prevention efforts. 6,7 Behavioral interventions that effectively produce reductions in risky sexual behavior and promote maintenance for safer sexual practice remain an important tool in fighting HIV.…”
Section: Introductionmentioning
confidence: 98%